2018
DOI: 10.1007/s10549-018-05085-9
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the cancer stem cell marker CD133 confers a poor prognosis in invasive breast cancer

Abstract: Purpose: CD133/ prominin 1 is a cancer stem cell marker associated with cancer progression and patient outcome in a variety of solid tumours, but its role in invasive breast cancer (BC) remains obscure. The current study aims to assess the prognostic value of CD133 expression in early invasive BC.Methods:CD133 mRNA was assessed in the METABRIC cohort and at the proteomic level using immunohistochemistry utilising a large well-characterised BC cohort. Association with clinicopathological characteristics, expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…At present, most studies have proved that CSCs are related to the recurrence, metastasis, and prognosis of tumors . Joseph et al found that the overexpression of CD133 as a surface marker of CSCs was positively correlated with proliferation of breast cancer cells, and negatively correlated with the patient's survival time. Bertolini found that CD133 + cell population in NSCLC was consistent with recurrence, metastasis, and high tumorigenicity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At present, most studies have proved that CSCs are related to the recurrence, metastasis, and prognosis of tumors . Joseph et al found that the overexpression of CD133 as a surface marker of CSCs was positively correlated with proliferation of breast cancer cells, and negatively correlated with the patient's survival time. Bertolini found that CD133 + cell population in NSCLC was consistent with recurrence, metastasis, and high tumorigenicity.…”
Section: Discussionmentioning
confidence: 97%
“…Cancer stem cells (CSCs) is a new theory put forward in recent years, which provides new ideas and ways to explore the occurrence and development of tumors . Most studies show that CSCs, which have a strong ability of self‐replication and self‐renewal, can promote tumor growth, migration, and invasion . Many studies also find that CSCs are closely related to tumor recurrence, metastasis, and treatment resistance .…”
Section: Introductionmentioning
confidence: 99%
“…CD133 has been reported to be a cancer stem cell marker in solid tumors [14,[32][33][34]. Several studies have shown that CD133 positive cells have the capacity for selfrenewal, differentiation, high proliferation, and forming tumors in xenografts [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…CD133 and Nestin have also been studied regarding their impact on prognosis in a range of solid tumors. For instances, overexpression of CD133 confers poor prognosis in invasive breast cancer, colorectal cancer, pancreatic cancer, etc . In addition, the negative impact of Nestin on survival has also been observed in lung cancer, esophageal squamous cancer, bladder cancer, etc .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, positive correlation was also observed between LGA, low-grade astrocytic tumors; HGA, high-grade astrocytic tumors cancer, colorectal cancer, pancreatic cancer, etc. [21][22][23] In addition, the negative impact of Nestin on survival has also been observed in lung cancer, esophageal squamous cancer, bladder cancer, etc. [24][25][26] Whereas in astrocytic tumor, the tumor of the central nervous system, the effects of CD133 and Nestin on prognosis are only discovered in a small volume of literatures.…”
Section: Discussionmentioning
confidence: 99%